The American lab : an insider's history of the Lawrence Livermore National Laboratory - Tarter, C. B. (Johns Hopkins nuclear history and contemporary affairs, 2018)
"In The American Lab, former LLNL director Bruce Tarter captures the spirit of the Laboratory and its reflection of the broader world in which it thrived. He identifies the major themes that have characterized science and technology in the latter half of the twentieth century--the growth and decline of nuclear warheads, the unprecedented rise of supercomputing technology, laser systems, fusion, and mass spectrometry. He illuminates the Cold War dynamic from the participants' point of view--an unusual and valuable perspective on nuclear history. The story of the laboratory is a tale of three eras. Although the Lab took its research vision from European Edward Teller, its modus operandi came almost exclusively from namesake Ernest Lawrence and was subsequently invented in-house by its scientists and staff. During its first two decades the Lab's focus was almost entirely on nuclear weapons research and development, with a few other smaller enterprises that were technically related to the nuclear weapons activities. In the 1970s and 1980s, the Laboratory, along with many others in the Department of Energy complex, expanded into civilian pursuits that included energy, environment, biology, and basic science. A major program in laser science and technology became a cornerstone of this period. The third era was initiated by the end of the Cold War and saw the transformation of the traditional nuclear weapons activities into the stockpile stewardship program along with the rapid growth of projects that can be broadly characterized as homeland security. Tarter's history/memoir of the Lawrence Livermore National Laboratory, provides an insider's examination of nuclear science in the Cold War and the technological shift that occurred after the fall of the Berlin Wall."--Provided by publisher